SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN PEJABAT STRUKTURAL PERGURUAN TINGGI DENGAN METODE SIMPLE MULTI ATTRIBUTE RATING TECHNIQUE (SMART) DI UNIVERSITAS MUHAMMADIYAH GORONTALO - Syaifuddin Syaifuddin; Moh. Rezky Himawan (Jurnal Informatika Upgris, 2020)
Colleges have not only played a role in education, but also on social aspects. Because a professional-managed college will bear value and trust for the public. There is an indication that the person who occupies any position, especially for the leaders of universities such as rector, Vice-Rector, Dean, Deputy Dean, majors, Secretary of the Department should have the ability and competence that qualified to be worthy to occupy the office. The University of Muhammadiyah Gorontalo (UMGO) is one of the emerging private colleges and continues to reform both in terms of quality and quantity, the method of research used is descriptive. The results of the study were implemented at the Muhammadiyah University of Gorontalo to assist with decision making.